Toward organizational integrity measurement: Developing a theoretical model of organizational integrity - Madeleine J. Fuerst; Christoph Luetge; Raphael Max; Alexander Kriebitz (Business and Society Review, 2023)
Organizational integrity is a key concept with and through which a company can assume its responsibility for ethical and societal issues. It is a basic premise for sustainable corporate success, as ethical risks ultimately become economic risks for a company. Recent research shows the potential of integrity-based governance models to reduce corporate risks and to improve business performance. However, companies are not yet able to assess nor evaluate their level of organizational integrity in a sound and systematic way. We aim to develop a theoretical model as a basis for the measurement of organizational integrity by conceptualizing the construct and sizing the theoretical model's scope. We suggest that the theoretical model follows a holistic approach and involves three types of dimensions: prerequisite dimensions, independent dimensions, and dependent dimensions. The organizational integrity triad—consisting of active commitments to self-imposed norms and principles, their transparent institutionalization into corporate processes and structures, and their implementation into action—plays a key role in this context.
Keywords: 330; business ethics; measurement; organizational integrity; theoretical model